PERBEDAAN PENGETAHUAN DAN KETRAMPILAN PESERTA TERHADAP PENYUSUNAN STRUKTUR ORGANISASI SEBELUM DAN SESUDAH PELATIHAN - Sarwo Edy Handoyo; Herlin Tundjung Setijaningsih; Sukis Warningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Religious organizations such as the youth organization of the mosque have a strategic role in the prosperity of the mosque. The prosperous mosque is marked by the lively worship activities of its worshipers. In Al Barokah Mosque, Cobodas Sub-District, Tangerang City, the organization of mosque teenagers is not running well and regularly. Based on observations and interviews with administrators of the Mosque Prosperity Board, the root of the problem is the lack of knowledge to compile an effective and efficient youth organization structure of the mosque. The solution offered to the target partners is the need to hold a training outlining the work to achieve organizational goals and training in the organization of the mosque's youth organization. By conducting training activities, the organizational structure of mosque teenagers can be structured as a basis for determining the right people to fill the positions listed on the organizational chart. Organizations that are managed by the right people will produce activities that are able to meet the expectations of mosque worshipers. The training was able to increase the knowledge and skills of participants to develop the organizational structure of mosque youth for the prosperity of the mosque. Improving the skills of the trainees includes skills about describing indicators of organizational goals, types of activities, grouping of activities, describing interactions in the organization and job descriptions and specifications. In addition, the trainees experienced an increase in knowledge related to the concept of the role of management in achieving organizational goals, management functions specifically organizing, organizational structure, the right man in the right place, and the rights and obligations of management and members of the organizationABSTRAK:Organisasi keagamaan seperti organisasi remaja masjid memiliki peran yang strategis terhadap kemakmuran masjid. Masjid yang makmur ditandai dengan semaraknya kegiatan ibadah para jamaahnya. Di Masjid Al Barokah, Kecamatan Cobodas, Kota Tangerang Banten organisasi remaja masjidnya kurang berjalan dengan teratur dan tearah. Berdasarkan observasi dan wawancara dengan pengurus Dewan Kemakmuran Masjid, akar permasalahannya adalah kurangnya pengetahuan untuk menyusun struktur organisasi remaja masjid yang efektif dan efisien. Solusi yang ditawarkan kepada mitra sasaran adalah perlu diadakannya pelatihan menguraikan pekerjaan untuk mencapai tujuan organisasi dan pelatihan penyusunan struktur organisasi remaja masjid. Dengan dilakukan kegiatan pelatihan maka dapat tersusun struktur organisasi remaja masjid sebagai dasar menentukan orang-orang yang tepat untuk mengisi jabatan yang tercantum pada bagan organisasi. Organisasi yang dikelola orang yang tepat akan menghasilkan kegiatan yang mampu memenuhi harapan jamaah masjid. Pelatihan mampu meningkatkan pengetahuan dan ketrampilan peserta untuk menyusun struktur organisasi remaja masjid untuk kemakmuran masjid. Peningkatan ketrampilan peserta pelatihan meliputi ketrampilan tentang menguraikan indikator tujuan organisasi, jenis kegiatan, pengelompokkan kegiatan, penggambaran interaksi dalam organisasi serta deskripsi dan spesifikasi jabatan. Selain itu peserta pelatihan mengalami peningkatan pengetahuan terkait dengan konsep tentang peran manajemen dalam mencapai tujuan organisasi, fungsi manajemen khususnya pengorganisasian, struktur organisasi, the right man in the right place, serta hak dan kewajiban pengurus dan anggota organisasi